Practice habits among guitar students in Faculty of Music UiTM Shah Alam / Ainnur Nadirah Mohd Shukor - Mohd Shukor, Ainnur Nadirah (2019)
Practice habits are training that doing in repeatedly which means every exercise that students play are be repeated. The aim of practice is to improve playing. Practices for every instruments need to be in a healthier way and with a right techniques so that the practicing will develop a good playing and also can avoid from the injuries. The purpose of this study is to investigate the practice habits and the position of practicing among guitar students. The sample for this study is 50 respondents of the diploma and degree students (n=50) from the Faculty of Music, UiTM Shah Alam.